Analysis of Groundwater Quality Using Water Quality Index (WQI) and Geographic Information System (GIS) Techniques: A Case Study of Boarding Area Near Hasanuddin University, Makassar (Workshop and Sahabat) - Muhammad Fawzy Ismullah Massinai; Andri Moh. Wahyu Laode; Iswatun Khazanah; Devi Cintya Andini (Universitas Muhammadiyah Mataram, 2021)
The importance and high demand of groundwater, in this case, the well water in the boarding area near Hasanuddin University is not supported by the data to ensure that the water quality in the area is sufficient and suitable for use. Several parameters are needed to determine the quality of groundwater in the area, such as pH, Turbidity, Lead (Pb), Antimony (Sb), Molybdenum (Mo), and Uranium (U). The methods used in this study are Water Quality Index (WQI) and Geographic Information System (GIS), combined with literature review results and field data. This study shows that the WQI index value of the second sample point (Workshop) is 51.76666667, which is classified as a C rating (poor water quality), and the seventh sample point (Sahabat) is the worst with an index value of 76.35185185, which is classified as a D rating (very poor water quality). These results indicate that land use and population will affect the water quality in the study area.